2014
DOI: 10.1038/jp.2013.137
|View full text |Cite
|
Sign up to set email alerts
|

Hemimelia and absence of the peroneal artery

Abstract: The arterial patterns of the lower extremities of three patients with congenital absence fibulae (hemimelia) were evaluated to determine whether the relationship existed between the absence of peroneal artery and hemimelia. Computerized tomograph angiography revealed the absence of peroneal artery in all the patients with dysplastic limbs and absent fibula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Other associations that are seen include a hypoplastic, subluxed, or dislocated patella; agenesis of cruciate ligaments; hypoplastic femoral condyles; and major vascular anomalies (11,39,40). The principal vascular abnormalities of patients with FH are the absence of the anterior tibialis and dorsalis pedis arteries (39).…”
Section: Associations Of Fhmentioning
confidence: 95%
“…Other associations that are seen include a hypoplastic, subluxed, or dislocated patella; agenesis of cruciate ligaments; hypoplastic femoral condyles; and major vascular anomalies (11,39,40). The principal vascular abnormalities of patients with FH are the absence of the anterior tibialis and dorsalis pedis arteries (39).…”
Section: Associations Of Fhmentioning
confidence: 95%
“…The skeletal pathologies are manifested by dysmorphic bony patterns, which, interestingly, correspond closely to the embryonic arterial in-growth pattern of the late embryonic limb, ascribed to Senior (Senior, 1919a(Senior, , 1919b(Senior, , 1985. Associated deficiencies of development of proper nutrient arteries, associated with retained embryonic arterial patterns, correspond to a proposed syndromic prototypical pattern of long bone reductions of the femur (profunda femoris artery) (Hootnick et al, 1983), fibula (peroneal artery) (Bedoya et al, 2015;Hootnick et al, 1980b;Huda et al, 2014), and midline metatarsals (medial deep plantar arterial arch) (Hootnick et al, 1980a(Hootnick et al, , 1983Levinsohn et al, 1991;Sarrafian & Kelikian, 2011).…”
Section: Vascular Injury As a Mechanism For Embryonic Bone Loss Andmentioning
confidence: 97%
“…Congenital arterial anomalies have been independently reported as associated with an asymmetric, noncontiguous pattern of congenital femoral (Chomiak et al, 2009), fibular (Bedoya et al, 2015;Hootnick et al, 1980b;Huda et al, 2014), and midline metatarsal (Hootnick, 2014;Hootnick, Packard, & Levinsohn, 1983;Hootnick et al, 1980a) long bone deficiencies. The skeletal pathologies are manifested by dysmorphic bony patterns, which, interestingly, correspond closely to the embryonic arterial in-growth pattern of the late embryonic limb, ascribed to Senior (Senior, 1919a(Senior, , 1919b(Senior, , 1985.…”
Section: Vascular Injury As a Mechanism For Embryonic Bone Loss Andmentioning
confidence: 99%
“…Although there were no supporting images, the authors alleged that there were absences of the ATA in two limbs and an anomalous arterial pattern in one limb (Caskey & Lester, 2002). An incomplete arteriographic study (Huda et al, 2014) of a single CSL with fibular deficiency contained a single inadequate image, which reveals radiographic absence of both the fibula and the PA. Other MR imaging of a variety of congenital lower limb deformities included five fibular deficient limbs (Laor, Jaramillo, Hoffer, & Kasser, 1996); the authors reported 8 out of 9 absent or abnormal popliteal trifurcations. One fibular deficient limb exhibited "vascular hypoplasia," confirmed by an unpublished angiography (Laor et al, 1996).…”
Section: Arteriography Of the Fibular Deficient Cslmentioning
confidence: 99%